Catechin-incorporated dental copolymers inhibit growth of Streptococcus mutans - Alexandra Mankovskaia; Celine M. Levesque; Anuradha Prakki (University of São Paulo, 2013)
Objective: To test the inhibitory growth activity of green tea catechin incorporated into dental resins compared to resins containing the broad-spectrum antimicrobial compound chlorhexidine against Streptococcus mutans in vitro. Material and Methods: The minimum inhibitory concentrations (MICs) of epigallocatechin-gallate (EGCg) and chlorhexidine (CHX) were determined according to the microdilution method. Resin discs (5 mm × 3 mm) were prepared from Bis-GMA/TEGDMA (R1) and Bis-GMA/CH3Bis-GMA (R2) comonomers (n=9) containing: a) no drug, b) EGCg, c) CHX. Two concentrations of each drug (0.5× MIC and 1× MIC) were incorporated into the resin discs. Samples were individually immersed in a bacterial culture and incubated for 24 h at 37°C under constant agitation. Cell viability was assessed by counting the number of colonies on replica agar plates. Statistical analysis was performed using one-way ANOVA, Tukey and Student t-tests (α=0.05). Results: Both resins containing EGCg and CHX showed a significant inhibition of bacterial growth at both concentrations tested (p<0.05). A significantly higher inhibition was observed in response to resins containing CHX at 0.5× MIC and 1× MIC, and EGCg at 1× MIC when compared to EGCg at 0.5× MIC. Also, EGCg at 0.5× MIC in R1 had a significantly higher growth inhibition than in R2. Conclusions: Both EGCg and CHX retained their antibacterial activity when incorporated into the resin matrix. EGCg at 1× MIC in R1 and R2 resins significantly reduced S. mutans survival at a level similar to CHX. The data generated from this study will provide advances in the field of bioactive dental materials with the potential of improving the lifespan of resin-based restorations.